2017
DOI: 10.1002/ijop.12443
|View full text |Cite
|
Sign up to set email alerts
|

Measuring generalised expectancies for negative mood regulation in China: The Chinese language Negative Mood Regulation scale

Abstract: Negative mood regulation expectancies (NMRE) represent people's confidence that they can alleviate their negative affect or induce a positive emotional state through thought or action. NMRE predict coping behaviour and mood outcomes for individuals under stress. Since 1990, much research documents the reliability and validity of the English language Negative Mood Regulation (NMR) scale as a measure of NMRE. The current research reports two studies developing a Chinese language translation of the NMR (NMR-C) sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 21 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…Drawing on the findings from prior studies, the 154 items from six frequently employed Chinese-versions of self-report ER measures were used to build the initial CAT-ER item bank ( Table 2). The ER measures used in this study included the DERS (Li and Wu, 2018), TMMS (Li et al, 2002), RESE (Wen et al, 2009), ERQ (Li and Wu, 2018), CERQ (Zhu et al, 2008), and NMR (Wang et al, 2017). Example items of the DERS are "I am clear about my feelings" and "When I'm upset, I believe my emotions are valid and important."…”
Section: Methodsmentioning
confidence: 99%
“…Drawing on the findings from prior studies, the 154 items from six frequently employed Chinese-versions of self-report ER measures were used to build the initial CAT-ER item bank ( Table 2). The ER measures used in this study included the DERS (Li and Wu, 2018), TMMS (Li et al, 2002), RESE (Wen et al, 2009), ERQ (Li and Wu, 2018), CERQ (Zhu et al, 2008), and NMR (Wang et al, 2017). Example items of the DERS are "I am clear about my feelings" and "When I'm upset, I believe my emotions are valid and important."…”
Section: Methodsmentioning
confidence: 99%
“…The study for validity evidence of the original scale indicated adequate internal consistency, with a reliability coefficient ranging from .87 to .93 (Catanzaro & Mearns, 1990). Other translated and culturally adapted versions also presented evidence of adequate psychometric validity, with reliability coefficients between .88 and .93 (Backenstrass et al, 2010;Mearns et al, 2013;Mearns et al, 2016;Pfeiffer et al, 2012;Wang et al, 2017). In addition, scale validity evidence studies conducted in different languages have reported construct validity evidence, based on associations with external variables.…”
mentioning
confidence: 93%
“…The NMR-S scale has been used in different international studies, and has been reported as a relevant, empirically-based measure for evaluation of emotion regulation characteristics Gratz & Roemer, 2004;Weiss et al, 2015). The scale has already been translated into different languages, including German (Backenstrass et al, 2010), Spanish (Pfeiffer et al, 2012), Hebrew (Orbach et al, 2007), Korean (Mearns et al, 2013), Japanese (Mearns et al, 2016), Greek (Kanavou, 2019), Hindi (Dubey et al, 2013) and Chinese (Wang et al, 2017).…”
mentioning
confidence: 99%
See 2 more Smart Citations